Establishment of Land Court in Indonesia: an effort to realise justice based on Pancasila - Fathoni, M. Yazid; Vasalo, Acacio Fernandez (CV. Ius et Ambientis, 2023)
The complexity of land problems is currently less able to be resolved by the general court so the handling of many land cases is incomplete. Otherwise, the land issues are not only related to private issues but are public and administrative. It is not surprising then that sometimes several court decisions can be attached to one land object, both from the ownership issued by the District Court and the Religious Court and from the administrative concerning the issuance of a certificate of title to the land by the State Administrative Court. This often provides a long time process and uncertain land ownership. This condition increasingly distances the parties from achieving a simple, fast, low-cost justice system and far from a settlement model based on the principles of Pancasila. This article will examine the urgency of establishing a land court to create a simple, fast, and low-cost land court, and a land dispute resolution model under the Pancasila values.